Isolation and Identification of Cellulolytic Bacteria from Gut of Horn Beetle Larvae (Oryctes rhinoceros L.) - Riskawati, Riskawati; Natsir, Hasnah; Dali, Seniwati; Baharuddin, Maswati (Universitas Jenderal Soedirman, 2023)
The horn beetle larvae (Oryctes rhinoceros L.) contain symbiotic bacteria that are used to digest and degrade cellulose as food so that it has the potential to produce cellulase enzymes. This study aims to isolate, characterize and identify microbial symbionts from horn beetle larvae that have the potential to produce cellulase enzymes.The methods in this study include morphology and physiology identification of bacteria, qualitative and quantitative activity tests and species determination using 16S rRNA sequencing technique. Based on the results of morphological observations, five bacterial isolates were taken which has the potential as a cellulase producer is indicated by the presence of a clear zone that is produced when a qualitative test is carried out using congo red staining with different cellulolytic indices. Based on the quantitative bacterial activity test using UV-Vis, the highest activity was found in PES3 isolates at 1.62 x 10-2 and PES5 at 1.61 x 10-2. Species determination results found that PES3 isolates belonged to the genus Acinetobacter and PES5 belonged to Pseudomonas. In addition to the isolates obtained for the environment and the industrial sector, cellulolytic bacteria can provide added value such as hydrolyze cellulose waste into alternative fuels.